3D reconstruction of magnetization from dichroic soft X‐ray transmission tomography. (30th May 2018) - Hierro-Rodriguez, Aurelio; Gürsoy, Doga; Phatak, Charudatta; Quirós, Carlos; Sorrentino, Andrea; Álvarez-Prado, Luis Manuel; Vélez, Maria; Martín, José Ignacio; Alameda, José Maria; Pereiro, Eva; Ferrer, Salvador
Abstract : By using soft X‐ray transmission microscopy with magnetic contrast (magnetic circular dichroism) it is possible to obtain valuable magnetic information from the studied systems. In this work, in a step further, a method to use magnetic soft X‐ray transmission tomography as an ideal tool to reconstruct the three‐dimensional magnetization configuration of arbitrary magnetic samples is presented. Abstract : The development of magnetic nanostructures for applications in spintronics requires methods capable of visualizing their magnetization. Soft X‐ray magnetic imaging combined with circular magnetic dichroism allows nanostructures up to 100–300 nm in thickness to be probed with resolutions of 20–40 nm. Here a new iterative tomographic reconstruction method to extract the three‐dimensional magnetization configuration from tomographic projections is presented. The vector field is reconstructed by using a modified algebraic reconstruction approach based on solving a set of linear equations in an iterative manner. The application of this method is illustrated with two examples (magnetic nano‐disc and micro‐square heterostructure) along with comparison of error in reconstructions, and convergence of the algorithm.